Association of European plum varieties in the orchards - Szabó, Z.; Nyéki, J.; Andrásfalvy, A.; Soltész, M. (International Journal of Horticultural Science, 1999)
The flowering phenology, blooming time and inter-fertility relations of 63 European plum varieties has been studied at growing sites with different ecological conditions during a 10 year long period. The purpose was to develop a system of variety combinations which approaches an optimum in fertility as long as inter-fertility relations will cease to be a limiting factor of yield. According to their blooming time, varieties are assigned to 5 groups: very early, early, medium, late and very late. As for their fertility relations, four groups are formed: self-sterile (0%), partially self-fertile (0.1 to 10 %), self-fertile (10.1 to 20 %) and highly self-fertile (more than 20 % fruit set with self pollination). The four categories of fruit set at free pollination are also relevant to the grower: low (less than 10 %), medium (10 to 20 %), high (20 to 40 %) and very high (more than 40 % fruit set). By artificial cross pollination, one combination Cacanska najbolja x Stanley proved to be mutually inter-incompatible. Blocks planted to a single self-sterile variety flanking a pollinizer variety proved the spacial distribution of the pollen. The reduction in fruit set was already apparent in the second row away from the pollinizer trees. In a large plantation, without bee hives, relatively low yield was stated on self-sterile trees even close to the pollinizer. In the case of self-sterile and partially self-fertile varieties, a combination of three varieties is recommended. The blooming period of the pollinizer variety should overlap the period of the self-sterile variety at least by 70 %, and the distance should not exceed 15 to 20 meters. Association of self-fertile varieties may also enhance the productivity of the trees. In that case an overlap of 50 % in blooming time and a maximum distance between the varieties of 30 to 40 meters will be sufficient.